Hubungan antara Terpaan Berita Covid-19, Intensitas Interaksi Peer Group, Tingkat Pendidikan dengan Sikap Masyarakat Kepada Penderita Covid-19 - Setyabudi, Gunawan; Pradekso, Tandiyo; Yusriana, Amida (Interaksi Online, 2021)
The mass media has the power to disseminate information related to Covid-19 quickly and widely. In addition, peer group interaction and education level also contribute to determining the direction of the attitude of its members. This study aims to determine the relationship between exposure to Covid-19 news, the intensity of peer group interactions, education level and public attitudes towards Covid-19 sufferers. This study uses social learning theory and social category theory to determine the hypothesis. This study uses non-random sampling by means of grab sampling. The number of samples studied was 50 people, domiciled in the city of Semarang, following the news of Covid-19 and aged between 20-50 years. The results of the hypothesis test with multiple correlations show the number 0.165, which means that there is no simultaneous relationship between the variables of exposure to Covid-19 news, the intensity of peer group interactions and public attitudes towards Covid-19 sufferers. Through these findings, in order to create an attitude towards Covid-19 sufferers, it is suggested that the public does not need to worry about news related to Covid-19 sufferers, and the government, in this case as a communicator, needs to create a campaign strategy with a peer-led approach as an effort to encourage the public to not rejecting Covid-19 patient.